TINJAUAN KEJELASAN KELENGKAPAN PENULISAN DIAGNOSIS DALAM KETEPATAN PENGODEAN BERKAS PENDING KLAIM DI RSUD M.NATSIR SOLOK 2023 - yulfa yetno (Poltekkes Kemenkes Semarang, 2023)
ABSTRAKThe accuracy of the diagnosis code is the suitability of the diagnosis code set by the coding officer. The purpose of this study was to review the clarity and completeness of writing diagnoses in the accuracy of coding diagnoses in pending claim files at M.Natsir Solok Hospital. This research is quantitative with a descriptive approach. With a sample of pending claim diagnosis codes in patients at M.Natsir Solok General Hospital, there were 62 medical records, which were taken by means of saturated sampling technique. The analysis used is univariate analysis. The research results obtained, the clarity and completeness of the writing of the diagnosis, and the accuracy of the coding of the diagnosis in the pending claims file, found that as many (32.3%) wrote the diagnosis that was not clear and as many as (67.7%) had clarity in writing the diagnosis, and there were (32.3%) incomplete writing diagnosis and as many as 42 (67.7%) completeness of writing a diagnosis. And there were as many as (51.6%) with an incorrect diagnosis code and as many as (48.4%) with the correct diagnosis code. Therefore the researchers suggest that there is a need for a policy on coding officers and an evaluation of the clarity of doctors and the completeness of writing patient diagnoses.Keywords : Clarity and Completeness of Writing Diagnosis, Accuracy of Code ABSTRAKKetepatan kode diagnosis ialah kesesuaian kode diagnosis yang ditetapkan petugas koding. Tujuan penelitian ini ialah untuk mengetahui tinjauan kejelasan dan kelengkapan penulisan diagnosis dalam ketepatan pengodean diagnosis pada berkas pending klaim di RSUD M.Natsir Solok.Penelitian ini ialah kuantitatif dengan pendekatan deskriptif.Dengan sampel kode diagnosis pending klaim pada pasien di RSUD M.Natsir Solok sebanyak 62 rekam medis, yang diambil dengan cara teknik sampling jenuh. Analisa yang digunakan ialah analisa univariat.Hasil penelitian di dapatkan, kejelasan dan kelengkapan penulisan diagnosis, dan ketepatan pengodean diagnosis pada berkas pending klaim ialah ditemukan sebanyak (32.3%) penulisan diagnosis yang tidak jelas dan sebanyak (67.7%) memiliki kejelasan penulisan diagnosis, dan terdapat (32.3%) ketidaklengkapan penulisan diagnosis dan sebanyak 42 (67.7%) kelengkapan penulisan diagnosis. Serta terdapat sebanyak (51.6%) dengan kode dignosis yang tidak tepat dan sebanyak (48.4%) kode diagnosis yang tepat. Maka dari itu peneliti menyarankan diperlukan adanya kebijakan terhadap petugas coding dan adanya evaluasi terhadap kejelasan dokter dan kelengkapan penulisan diagnosis pasien.Kata Kunci :Kejelasan dan Kelengkapan Penulisan Diagnosis, Ketepatan Kode